1995
DOI: 10.1002/mc.2940140404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel phorbol ester‐ and serum‐responsive sequences of the rat ornithine decarboxylase gene promoter

Abstract: Ornithine decarboxylase (ODC), the key regulatory enzyme in mammalian polyamine biosynthesis, is rapidly induced by mitogens and tumor promoters. We used transient expression assays and DNA-protein binding studies to examine the regulation of ODC promoter activity by phorbol esters and serum growth factors. A fragment of the ODC 5' flanking region (nt-1156 to +13) was sufficient to confer 12-O-tetradecanoylphorbol-13-acetate (TPA)-responsive expression to a luciferase reporter gene when transfected into H35 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In contrast, a ®fth Sp1-binding site at nt À108 contributes little to ODC promoter activity [19]. Nevertheless, Sp1 is not required for induction of ODC by TPA because ODC promoter fragments lacking the Sp1-binding sites remain responsive to TPA [16]. However, Sp1 may play a role in overexpression of ODC during carcinogenesis because we found that Sp1 expression and DNAbinding activity are elevated in papillomas, carcinomas, and cell lines derived from epidermal tumors [21].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, a ®fth Sp1-binding site at nt À108 contributes little to ODC promoter activity [19]. Nevertheless, Sp1 is not required for induction of ODC by TPA because ODC promoter fragments lacking the Sp1-binding sites remain responsive to TPA [16]. However, Sp1 may play a role in overexpression of ODC during carcinogenesis because we found that Sp1 expression and DNAbinding activity are elevated in papillomas, carcinomas, and cell lines derived from epidermal tumors [21].…”
Section: Introductionmentioning
confidence: 57%
“…An ATF/CRE site is located at nt À50 to À43 of the ODC promoter and contributes to regulation of ODC transcription by protein kinase A [22]. However, mutation of this site does not signi®cantly affect the ratio of activity in TPAtreated cells relative to that in untreated cells (the induction ratio) [16]. Two conserved myc-binding sites in intron 1 of mammalian ODC genes have been shown to mediate induction of ODC by myc [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether the C/EBP␤ protein regulates transcription of the 24p3 and ODC genes, we next performed transient transfection experiments with the reporter plasmids pODClux1m (20) and p24p3luc, containing 1.2 and 0.8 kb, respectively, of the promoter regions of the ODC and 24p3 genes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The entire promoter fragment (Ϫ719 to ϩ18, p24p3) was subcloned in the promoterless luciferase reporter vector pXP1. The construct pODClux1m (containing 1.2 kb of the rat ODC promoter) was a gift of Dr. A. P. Butler (Anderson Cancer Center, University of Texas) (20).…”
Section: Cell Culture and Transfectionsmentioning
confidence: 99%